Getting our way : 500 years of adventure and intrigue, the inside story of British diplomacy - Meyer, Christopher
We have no eternal allies and we have no perpetual enemies. Our interests are eternal and perpetual, and those interests it is our duty to follow' -Lord Palmerston, 1848 This is a highly informed insider's account of some of the 'honest men' as they sought, by fair means or foul, to get Britain its way in the world.